PERANAN MOTIVASI DAN KOMPETENSI: ANALISIS KINERJA PEGAWAI PEMERINTAHAN DAERAH KABUPATEN PASER - Dedy Darmawan (Islamic University of Kalimantan MAB Banjarmasin, 2019)
This study aims to determine the effect of motivation variables (X1) and competence (X2) on employee performance (Y) simultaneously and partially in the Public Relations and Protocol Section of the Paser Regency Regional Secretariat. The analysis method uses multiple linear regression. The population in this study were all employees in the Public Relations and Protocol Section at the Paser Regency Regional Secretariat. The sample of this study was 32 people. Simultaneous testing shows that there is at least one independent variable (X), which affects the dependent variable. Furthermore, partial testing is carried out, which shows the effect of motivation (X1) has a significant effect on employee performance (Y) of 5.440. While the competency variable (X2) does not affect employee performance (Y). The adjusted R square is 0.472; which means that the variation of motivation (X1) and competence (X2) can explain the performance (Y) of 47.2% while the rest is explained by other unknown factors of 52.8%. Based on the results of the analysis, motivation (X1) is a very dominant variable affecting the performance of employees in the Public Relations and Protocol Section at the Paser Regency Regional Secretariat. This causes competence not to have a significant effect on employee performance.Keywords: motivation, competency and employee performance.